Gender-specific age-related changes in physical performance, physical activity and anthropometry status among community-dwelling older persons with and without mild cognitive impairment : a prospective study - Rajwinder Kaur Hardev Singh,; Devinder Kaur Ajit Singh,; Suzana Shahar, (Penerbit Universiti Kebangsaan Malaysia, 2022)
In this study, we aimed to determine gender specific age-related decline in anthropometry status, physical performance (PP) and physical activity (PA) in older persons with and without mild cognitive impairment (MCI) prospectively over 3 years. Within-group changes across three time points (baseline-Wave 1, 18 months-Wave 2, 36 months-Wave 3) based on gender and cognitive status were determined. Data was collected at Wave 3 of a longitudinal study: “Neuroprotective Model for Health Longevity among Elderly”. Secondary data from Wave 1 and 2 was obtained for analysis. Older persons with MCI were categorised to have subjective memory problems (answered ‘yes’ on item 10 of Geriatric Depression Scale), scored at least 1.5 SD below mean average on Rey Auditory Verbal Learning Test and Digit Span, no dementia, no problems with activities in daily living, intact global cognition (>19/30: Mini Mental State Examination) and without depression (Geriatric Depression Scale 15-items,≤4). Anthropometry measurements and a battery of PP tests were performed. PA was measured using Physical Activity Scale for the Elderly questionnaire. Data from 779 older persons (67.7 ± 5.3 years) consisting of 372 men (68.0 ± 5.2 years) and 407 women (67.4 ± 5.4) who completed all tests from Wave 1 to Wave 3 were analysed. There was a decline in PP (-0.7% to -14.1% per year), PA levels (-0.7% to -14.1% per year) and anthropometry status (-0.1% to -6.3% per year), except for percentage body fat (+9.9% per year) with advancing age. Within-group changes over the three years showed significant differences (p<0.05) in height and PA in non-MCI and MCI men and lower body flexibility in non-MCI and MCI women. Specifically, tailored physical and nutritional health prevention and promotion strategies for older persons based on gender and cognitive status may be beneficial to support person-centered care.